Lattice Boltzmann Simulations of Thermocapillary Motion of Droplets in Microfluidic Channels. (3rd June 2015) - Li, Jonathan; Liu, Haihu; Ioannou, Nikolaos; Zhang, Yonghao; Reese, Jason M.
Abstract Our recently developed lattice Boltzmann model is used to simulate droplet dynamical behaviour governed by thermocapillary force in microchannels. One key research challenge for developing droplet-based microfluidic systems is control of droplet motion and its dynamic behaviour. We numerically demonstrate that the thermocapillary force can be exploited for microdroplet manipulations including synchronisation, sorting, and splitting. This work indicates that the lattice Boltzmann method provides a promising design simulation tool for developing complex droplet-based microfluidic devices.